Coronary chronic total occlusion intervention: utility or futility. (4th May 2018) - Marechal, Patrick; Davin, Laurent; Gach, Olivier; Martinez, Christophe; Lempereur, Mathieu; Lhoest, Nicolas; Lancellotti, Patrizio
ABSTRACT: Introduction : Despite an incidence of about 18–52% of the patients undergoing coronary angiography, chronic total occlusions (CTO) are rarely revascularised by percutaneous angioplasty (PCI). Nevertheless, current evidence suggests that successful CTO angioplasty improves symptoms, quality of life and long-term survival. During the last decade, the improvement of specific tools and techniques for these complex procedures, and the increasing experience of operators, have led to the achievement of success and complication rates almost equivalent to non-CTO angioplasty. Areas covered : This review focuses on the clinical benefits of CTO revascularization and on appropriate patient selection. Expert commentary : Current evidence suggests that successful CTO-PCI improves symptoms, quality of life and long-term survival. During the last years, the improvement of specific techniques for these complex procedures and the increasing experience of operators, have led to the achievement of success and complication rates almost equivalent to non-CTO lesion angioplasty.